Statistical analysis of Pleistocene calcareous microplanktonic assemblages: an attempt for understanding the variations of environmental parameters - LUPI, CLAUDIA; COBIANCHI, MIRIAM; Luciani Valeria; BORDIGA, MANUELA (2011)
The application of a multivariate statistical approach to a database concerning the occurrence of the two major calcareous planktonic groups (calcareous nannofossils and foraminifera) provides a potential additional instrument to identify the variation over time of the sea surface water parameters.